2015
DOI: 10.1080/09571736.2015.1028088
|View full text |Cite
|
Sign up to set email alerts
|

L2 vocabulary learning and testing: the use of L1 translation versus L2 definition

Abstract: This paper investigates the effect of using L1 translations versus L2 definitions on the learning and testing of L2 vocabulary recognition knowledge. For this study, 48 Japanese L2 learners of English studied 200 lexical items from the academic word list (AWL) over a 10-week period. To support their learning, the participants were provided with the meaning of the target language. The language in which the meanings were presented was manipulated such that the learners received half of them in their L1 and half … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
24
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 29 publications
8
24
0
3
Order By: Relevance
“…Ramachandran and Abdul Rahim (2004) vividly show that translation is a very effective tool for teaching and learning L2 vocabulary. Ramachandran and Abdul Rahim's findings have been supported by a recent study conducted by Joyce (2015) who also found that translation techniques would boost the acquisition and retention of L2 lexical items. Kern (1994) is another study that investigated the role of translation in L2 acquisition and processing.…”
Section: Translationsupporting
confidence: 72%
“…Ramachandran and Abdul Rahim (2004) vividly show that translation is a very effective tool for teaching and learning L2 vocabulary. Ramachandran and Abdul Rahim's findings have been supported by a recent study conducted by Joyce (2015) who also found that translation techniques would boost the acquisition and retention of L2 lexical items. Kern (1994) is another study that investigated the role of translation in L2 acquisition and processing.…”
Section: Translationsupporting
confidence: 72%
“…They found that the translation method, i.e., the pedagogy of utilising the first language word equivalents in teaching new English vocabulary had positive effects on the students' vocabulary recall and retention. A similar outcome was found by Joyce (2015) in a study which involved English as Foreign Language (EFL) undergraduate students in Japan. These empirical evidences supported the notion that classroom code-switching could contribute to knowledge construction and transmission in the ESL and EFL classrooms (refer to a review by Ghobadi and Ghasemi, 2015).…”
Section: Introduction Classroom Code-switchingsupporting
confidence: 59%
“…In translating a written text, there are intralinguistic and extralinguistic factors that must be understood before the ideas of a writer are transferred to the target language. Language -as an object of translation-is part of culture, therefore translating from one language to another cannot be done adequately without having a good knowledge of the culture and structure of those two languages (Longinovic, 2002;Joyce, 2018;Ying et all., 2018;Mohammad et all., 2018).…”
Section: Introductionmentioning
confidence: 99%